2019
DOI: 10.21608/epsj.2019.48276
|View full text |Cite
|
Sign up to set email alerts
|

Improving Utilization of Acacia Leaves Meal and Its Effects on Broilers Performance.

Abstract: Two hundred and forty day old Cobb broiler chicks were distributed into eight groups; the experimental treatments were arranged in a factorial design (2x4) by using two levels of tartaric acid (0 and 0.30 %) and four levels of Acacia saligna leaves meal (ALM) L1, L2, L3 and L4 to be 0, 3, 6 and 9%, respectively. Results showed that supplemented broiler diets with 0.30%of tartaric acid improved digestion coefficients of CP, CF, NFE , DCP, live body weight , body gain ,feed conversion ,increased edible giblets%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Abd El-Galil et al (2018) observed that the inclusion of 8% Acacia saligna leaf meal in Mamourah growing hens diet resulted in higher net returns, percentage of economical efficiency, and relative economical efficiency of feed, and least feed cost of kg gain compared to other inclusion levels. Hassan and Abd El-Dayem. (2019) also found that 6% Acacia leaves meal in broiler diets improved economic efficiency % of feed and relative economic efficiency of feed compared to the control diet.…”
Section: Effect Of Tannins On Poultry Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abd El-Galil et al (2018) observed that the inclusion of 8% Acacia saligna leaf meal in Mamourah growing hens diet resulted in higher net returns, percentage of economical efficiency, and relative economical efficiency of feed, and least feed cost of kg gain compared to other inclusion levels. Hassan and Abd El-Dayem. (2019) also found that 6% Acacia leaves meal in broiler diets improved economic efficiency % of feed and relative economic efficiency of feed compared to the control diet.…”
Section: Effect Of Tannins On Poultry Productionmentioning
confidence: 99%
“…The most common Acacia species includes Acacia karroo, Acacia tortilis, Acacia nilotica, Acacia angustissima, Acacia saligna and Acacia scaffneri. Although they have high crude protein content, their utilisation, anti-nutritional factors (amount and types of tannins), viability, and palatability need to be taken into consideration as they affect animal performance (Mokoboki et al, 2005;Anon, 2009;Hassan and Abd El-Dayem, 2019). There is limited information about the use of various Acacia meals as alternative protein sources in poultry feeds to improve productivity and reduce feed costs.…”
Section: Introductionmentioning
confidence: 99%